Pengaruh Kompetensi Kerja terhadap Kinerja Berkelanjutan melalui Keunggulan Kompetitif Produk di Devano Silver Singapadu - Ni Putu Envira Noviari Nurika Shinta Dewi; I Made Adi Suwandana; I Gusti Putu Agung Widya Goca (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Sales dynamics, rising operational costs, failure to meet profit targets, the need for product rework, and the demand for products that keep pace with changing trends indicate that Devano Silver Singapadu still faces challenges in achieving sustainable performance. These conditions suggest that the company's sustainability is influenced not only by economic factors but also by its ability to manage internal resources to create product competitive advantage. This study aims to examine how work competence influences long-term performance through product competitive advantage at Devano Silver Singapadu. Partial Least Squares (PLS) analysis was employed as the quantitative method. Purposive sampling was used to select a sample of 120 respondents. The results indicate that work competence does not directly affect sustainable performance but has a positive and significant impact on product competitive advantage. Product competitive advantage positively and significantly influences sustainable performance and fully mediates the impact of work competence on sustainable performance. These findings suggest that work competence must first be translated into product competitive advantage to enhance the company's sustainable performance. It is recommended that Devano Silver Singapadu strengthen the technical competence of its artisans, enhance design innovation and product quality, optimize production process efficiency, and reinforce sustainability practices to continuously improve its competitiveness and business viability.